Effect of negative functionalisation of gold nanorods on conformation and activity of human serum albumin. Issue 5 (29th April 2019) - Alex, Sruthi Ann; Chandrasekaran, Natarajan; Mukherjee, Amitava
Abstract : The theranostic applications of gold nanorods (AuNRs) are limited due to the presence of cytotoxic cetrimonium bromide (CTAB) stabiliser, leading to the instigation of alternate stabilisers like negatively charged polystyrene sulphonate (PSS). Despite previous reports suggesting the impact of PSS‐AuNRs on cells, their effect on the most abundant protein in plasma, i.e. human serum albumin (HSA), has not been studied before. Hence, the impact of PSS‐AuNRs on HSA was thoroughly examined using varied spectroscopic techniques. The absorbance and fluorescence spectroscopic findings suggested the extent of ground‐state complexation and tryptophan domain disruptions of HSA for different AuNR concentrations, which were also suggested based on size measurements and activation energy calculations for complex formation. Modifications in the hydrophobic environment of HSA were evaluated using synchronous fluorescence, whereas the secondary structural damages were explained using circular dichroism (CD) and FTIR analyses. Additional studies to analyse protein denaturation, fibrillation, esterase activity, and free thiol were carried out to understand structural and functional changes. The study suggested that PSS‐AuNRs showed concentration‐dependent alterations in HSA structure, but the extent of protein toxicity was considerably lesser for PSS‐AuNRs of similar dimensions compared to the data available for CTAB‐AuNRs; thus, highlighting that PSS‐AuNRs could be safer for biomedical applications.